The number of lymphocytes increases in the periprosthetic tissues with increasing time of implant service in non-metal-on-metal total joint arthroplasties: A role of metallic particles - Hobza, Martin; Milde, David; Slobodová, Zuzana; Gallo, Jiří (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2021)
BACKGROUND: The objective of the study was to determine the association between periprosthetic concentrations of selected metals and changes induced in periprosthetic tissues (PT). METHODS: PT from 24 patients with metal-on-polyethylene or ceramic-on-polyethylene total joint replacements (TJRs) were examined. Samples underwent histological examination including quantification of cellular populations. Determination of metals was performed according to the published methodology. Results were processed using correlation analysis and Principal Component Analysis (PCA), respectively. RESULTS: Growing concentration of metals in the PT was found as a function of length of exposure (LoE). Differences in Ti, Co, Cr and V concentrations (per α = 0.05) depended on the type of alloy the implants were made from. On the contrary, the implant composition did not reflect in the different numbers of immune cells per 1 high power field, not even in distribution of the membrane type according to the Krenn classification. PCA revealed several clusters in dependence on the LoE, type of the membrane and presence of immune cells. High representation of lymphocytes in the PT was typical for clusters with the longest LoE while a higher representation of neutrophils was typical for a shorter time to reoperation. CONCLUSIONS: Correlation between the LoE and concentrations of metals in its surroundings was demonstrated. However, the tissue image analysis cannot differentiate finer, potentially metal-induced tissue changes. Importantly, the tissues become more similar with an increasing LoE. We draw a conclusion about predominantly non-specific stimulation of the PT jointly by metal and polyethylene particles in non-metal-on-metal TJRs.
Keywords: Metals; Lymphocytes; Reoperation; Prosthesis Failure; náhrada kyčelního kloubu; Polyethylenes; reoperace; lidé; Arthroplasty, Replacement, Hip; lymfocyty; kyčelní protézy; selhání protézy; Prosthesis Design; Hip Prosthesis; polyethyleny; kovy; protézy - design; Humans